Constitutional Court and Enforcement of Constitutional Rights in the Fourth Revision of the Mining Law - Kusmayanti, Shanti; Ardhanariswari , Riris; Kunarti, Siti; Nasihuddin, Abdul Aziz (As-Siyasi: Journal of Constitutional Law, 2025)
The fourth amendment to Law No. 4 of 2009 on Mineral and Coal Mining (Mining Law) has provoked widespread public criticism amid persistent mining-related problems, including land dispossession, environmental degradation, pollution, structural poverty, and the criminalization of local communities. These issues are intensified by the government’s limited responsiveness to public concerns, notwithstanding the Constitutional Court’s affirmation that state control over natural resources, as mandated by Article 33 of the 1945 Constitution, must constitute the fundamental basis for their management and utilization. This study aims to evaluate whether the fourth revision of the Mining Law has positive or negative impacts on society and the environment, and to examine the Constitutional Court's role in addressing constitutional issues arising from the law. The research employs a normative juridical approach, analyzing statutory regulations, supported by a literature review and a conceptual framework to interpret the principles of natural resource governance and environmental justice. The findings reveal that the revised Mining Law continues to contain substantial deficiencies, particularly regarding transparency, public participation, and the centralization of licensing authority at the national level. Such provisions weaken the role of local governments and restrict public oversight of mining activities. This study concludes that further harmonization of the Mining Law with constitutional principles is necessary, alongside strengthened environmental protection and a more inclusive policymaking process. In this regard, the Constitutional Court plays a crucial role as the guardian of the Constitution, ensuring that natural resource governance remains consistent with Article 33 of the 1945 Constitution and oriented toward sustainable and equitable prosperity.